"Not Another Meeting!" Are Meeting Time Demands Related to Employee Well-Being? - Rogelberg, Steven G.; Leach, Desmond J.; Warr, Peter B.; Burnfield, Jennifer L. (Journal of Applied Psychology, 2006)
Using an interruptions framework, this article proposes and tests a set of hypotheses concerning the relationship of meeting time demands with job attitudes and well-being (JAWB). Two Internet surveys were administered to employees who worked 35 hr or more per week. Study 1 examined prescheduled meetings attended in a typical week (N=676), whereas Study 2 investigated prescheduled meetings attended during the current day (N=304). As proposed, the relationship between meeting time demands and JAWB was moderated by task interdependence, meeting experience quality, and accomplishment striving. However, results were somewhat dependent on the time frame of a study and the operational definition used for meeting time demands. Furthermore, perceived meeting effectiveness was found to have a strong, direct relationship with JAWB.